Knowledge and Attitude of Intensive Care Nurses regarding the Prevention of Pressure Ulcer - SH Khojastehfar; T Najafi Ghezeljeh; SH Haghani (Iran University of Medical Sciences, 2019)
Background & Aim: Pressure ulcers are one of the indicators of the quality of nursing and health care. Nurses, as one of the main members of the health team, play an important role in the prevention of pressure ulcer in health care centers. Therefore, this study aimed to determine the knowledge, attitude, and practice of nurses in preventing pressure ulcer. Materials & Methods: This descriptive cross-sectional study was conducted in 2018. Through complete enumeration, all the employed intensive care unit nurses in the educational centers of Iran University of Medical Sciences were studied. Out of the 328 questionnaires, 308 questionnaires were completed by the participants. For data collection, Pieper Pressure Ulcer Knowledge Test (PPUKT) and Beeckman et al's attitude toward pressure ulcer questionnaire were used. Data were analyzed by SPSS software version 16, using independent t-test, Chi-square, Fisher's exact, and one-way ANOVA. Results: According to the results, the mean score of knowledge and attitude of nurses regarding the prevention of pressure ulcer were 63.10 ± 47.31, 39.39 ± 10.22, respectively. The knowledge and attitude of the majority of nurses, regarding the prevention of pressure ulcer was at an undesirable level. Different groups of gender, background of continuous education, work experience, and experience in ICU had a significant difference in knowledge score. There were significant differences between different groups of gender, working hours per week, work experience, and work experience in ICU in terms of attitude score. Conclusion: Considering the undesirable level of knowledge and attitude of nurses about the standards of prevention of pressure ulcers and the importance of improving the safety of patients admitted to the intensive care unit, it is suggested to develop appropriate educational planning to improve the knowledge and attitude of health care providers, especially nurses, in the area of prevention of pressure ulcer.